Recent advances in hole-spin qubits. (17th March 2023) - Fang, Yinan; Philippopoulos, Pericles; Culcer, Dimitrie; Coish, W A; Chesi, Stefano
Abstract: In recent years, hole-spin qubits based on semiconductor quantum dots have advanced at a rapid pace. We first review the main potential advantages of these hole-spin qubits with respect to their electron-spin counterparts and give a general theoretical framework describing them. The basic features of spin–orbit coupling and hyperfine interaction in the valence band are discussed, together with consequences on coherence and spin manipulation. In the second part of the article, we provide a survey of experimental realizations, which spans a relatively broad spectrum of devices based on GaAs, Si and Si/Ge heterostructures. We conclude with a brief outlook.